2007
DOI: 10.2967/jnumed.107.043703
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of VPAC1 Expression in Experimental and Spontaneous Prostate Cancer

Abstract: Among U.S. men, prostate cancer (PC) accounts for 29% of all newly diagnosed cancers. A reliable scintigraphic agent to image PC and its metastatic or recurrent lesions and to determine the effectiveness of its treatment will contribute to the management of this disease. All PC overexpresses VPAC1 receptors. This investigation evaluated a probe specific for a 64 Cu-labeled receptor for PET imaging of experimental human PC in athymic nude mice and spontaneously grown PC in transgenic mice. Methods: The probe, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 29 publications
1
48
1
Order By: Relevance
“…Vasoactive intestinal peptide/growth hormone-releasing hormone (VIP/ GHRH) antagonists, such as JV-1-52 and JV-1-53 constructed by our group, were also able to inhibit the growth of androgenindependent prostate cancers by abrogating the autocrine/ paracrine mitogenic stimuli of VIP (16). In prostate cancers, a probe specific for a 64 Cu-labeled receptor for PET imaging delineated xenografts and cases of occult prostate carcinoma that were not detectable with 18 F-FDG (17). It was shown that the VPAC1 receptor density in human lung cancer cell lines is unusually high being comparable to the density of tyrosine kinase receptors (6,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasoactive intestinal peptide/growth hormone-releasing hormone (VIP/ GHRH) antagonists, such as JV-1-52 and JV-1-53 constructed by our group, were also able to inhibit the growth of androgenindependent prostate cancers by abrogating the autocrine/ paracrine mitogenic stimuli of VIP (16). In prostate cancers, a probe specific for a 64 Cu-labeled receptor for PET imaging delineated xenografts and cases of occult prostate carcinoma that were not detectable with 18 F-FDG (17). It was shown that the VPAC1 receptor density in human lung cancer cell lines is unusually high being comparable to the density of tyrosine kinase receptors (6,18).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence of high density VPAC1 receptors in various cancers including SCLC and NSCLC, radiolabeled VIP analogs were used to localize various primary tumors and their metastases (5,6,17,20). However, it remains to be determined if a radiolabeled VIP analog can be useful for the early detection of lung cancer.…”
Section: Cancer Tissuementioning
confidence: 99%
“…Furthermore, VPAC1 antagonists inhibit the proliferation of breast cancer and lung cancer cells in vitro [40]. In the light of the VPAC1 overexpression in prostate and breast cancer, an experiment was performed using a VPAC1 agonist to visualize tumor localization [42].…”
Section: Physiological Activitiesmentioning
confidence: 99%
“…2,3 Small molecules such as sugars, amino acids, nucleic acids, or receptorbinding ligands are labeled with positron-emitting radionuclides for PET imaging to study in vivo visualization of physiological processes on a molecular level. [4][5][6][7] There are several positron-emitting radionuclides like fluorine- 18 Ga] generator, has drawn considerable attention for oncologic diagnostic applications. The short physical half-life of 68 Ga induces low radiation burden on patients and makes it an ideal radionuclide for diagnostic use.…”
mentioning
confidence: 99%
“…15 In the past few years, this laboratory has designed, synthesized, and radiolabeled peptide conjugates that have high affinity for VPAC1 receptors, overexpressed in many malignant tumors, including those of the breast and prostate. [16][17][18][19][20] The peptides are analogues of pituitary adenylate cyclase-activating peptide (PACAP)-a 27 amino acid peptide and vasoactive intestinal peptide (VIP)-28 amino acid. Both have similar biochemical properties and bind to VPAC1 receptors expressed in high density on the surface of certain cancers such as of the breast, prostate, and urinary bladder (100%), colon (96%), pancreas (65%), lung (58%), stomach (54%), and liver (49%).…”
mentioning
confidence: 99%